2009
DOI: 10.1007/s00382-009-0631-7
|View full text |Cite
|
Sign up to set email alerts
|

Ocean temperature and salinity components of the Madden–Julian oscillation observed by Argo floats

Abstract: New diagnostics of the Madden-Julian oscillation (MJO) cycle in ocean temperature and, for the first time, salinity are presented. The MJO composites are based on 4 years of gridded Argo float data from [2003][2004][2005][2006], and extend from the surface to 1400 m depth in the tropical Indian and Pacific Oceans. The MJO surface salinity anomalies are consistent with precipitation minus evaporation fluxes in the Indian Ocean, and with anomalous zonal advection in the Pacific. The Argo sea surface temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 51 publications
7
64
1
Order By: Relevance
“…These anomalies are maximum around 100 m depth but extend coherently into the deep ocean with a slight westward tilt with increasing depth. This tilt implies upward phase propagation and downward energy propagation and has been observed in equatorial Kelvin waves for the Pacific Ocean forced by the MJO (Matthews et al 2007(Matthews et al , 2010. The coherent propagation across the width of the Indian Ocean reinforces the hypothesis that the wave activity can be traced back to reflection of the equatorial Kelvin wave incident on the eastern boundary prior to day −100.…”
Section: Rossby Wave Vertical Structuresupporting
confidence: 76%
“…These anomalies are maximum around 100 m depth but extend coherently into the deep ocean with a slight westward tilt with increasing depth. This tilt implies upward phase propagation and downward energy propagation and has been observed in equatorial Kelvin waves for the Pacific Ocean forced by the MJO (Matthews et al 2007(Matthews et al , 2010. The coherent propagation across the width of the Indian Ocean reinforces the hypothesis that the wave activity can be traced back to reflection of the equatorial Kelvin wave incident on the eastern boundary prior to day −100.…”
Section: Rossby Wave Vertical Structuresupporting
confidence: 76%
“…The anomalies in both vertical velocity and density extend down below 300 m (Figure 4(f)), associated with downward propagation of wave energy into the deep ocean, consistent with the results of Matthews et al (2007Matthews et al ( , 2010. The westward tilt of the anomalies with depth is consistent with upward phase propagation and downward energy propagation.…”
Section: Case-studiessupporting
confidence: 75%
“…This study revealed that patterns of anomalous mixed layer temperature in the Indian and western Pacific Oceans are consistent with being forced by anomalies in heat flux that arise from MJO convective and wind anomalies. In addition, Matthews et al (2010) showed that subsurface salinity variations at MJO time scales, which are dominated by anomalies in precipitation minus evaporation in the Indian Ocean and zonal advection in the western Pacific Ocean, have different spatial and temporal characteristics than those of temperature. This implies that there may be variations in the upper-ocean density structure, and thus MLD, at MJO time scales.…”
Section: Introductionmentioning
confidence: 98%
“…Those studies that did include in situ subsurface observations have primarily been limited to mooring sites (e.g., Anderson et al 1996;Zhang and McPhaden 2000;Vialard et al 2008) or the inclusion of Argo profiling floats in a small regional domain (e.g., Han et al 2007;Vinayachandran and Saji 2008;Sato et al 2011), and very few studies have used in situ observations to characterize the MJO signal over a large domain. Matthews et al (2010) used Argo data to characterize MJO-related anomalies of temperature and salinity throughout the water column. This study revealed that patterns of anomalous mixed layer temperature in the Indian and western Pacific Oceans are consistent with being forced by anomalies in heat flux that arise from MJO convective and wind anomalies.…”
Section: Introductionmentioning
confidence: 99%